International capital market frictions and spillovers from quantitative easing. (February 2017) - MacDonald, Margaux
Highlights: Establishes that there is significant heterogeneity in how the Fed's LSAPs affected EME asset prices. Finds that bilateral capital market frictions vis-à-vis the U.S. are significant in explaining this heterogeneity. Finds that spillovers to EME asset prices were driven primarily by purchases of U.S. Treasury securities. Finds that other foreign quantitative easing programs show a similar pattern and effect on EME asset prices. Abstract: This paper analyzes the impact of large-scale, unconventional asset purchases by advanced country central banks on emerging market economies (EMEs) from 2008 to 2014. I show that there was substantial heterogeneity in the way these purchases affected EME currency, equity, and long-term sovereign bond markets. Drawing on the gravity-in-international-finance literature, I show that the degree of capital market frictions between EMEs and advanced countries is significant in explaining the observed heterogeneity in how these asset prices were affected. This result is robust to considerations of domestic monetary policy, exchange rate regime, and capital control policies in EMEs. Furthermore, I show that the size and direction of asset price movements in EMEs depended both on the type of assets purchased and on whether it was the U.S. Federal Reserve or other advanced country central banks engaging in the purchases.